If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -3(2x + 6) = 6 + -5x Reorder the terms: X + -3(6 + 2x) = 6 + -5x X + (6 * -3 + 2x * -3) = 6 + -5x X + (-18 + -6x) = 6 + -5x Reorder the terms: -18 + X + -6x = 6 + -5x Solving -18 + X + -6x = 6 + -5x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '18' to each side of the equation. -18 + X + 18 + -6x = 6 + 18 + -5x Reorder the terms: -18 + 18 + X + -6x = 6 + 18 + -5x Combine like terms: -18 + 18 = 0 0 + X + -6x = 6 + 18 + -5x X + -6x = 6 + 18 + -5x Combine like terms: 6 + 18 = 24 X + -6x = 24 + -5x Add '6x' to each side of the equation. X + -6x + 6x = 24 + -5x + 6x Combine like terms: -6x + 6x = 0 X + 0 = 24 + -5x + 6x X = 24 + -5x + 6x Combine like terms: -5x + 6x = 1x X = 24 + 1x Simplifying X = 24 + 1x
| -0.771-2n+3.69=n-3.6 | | 11x+16+5y-7=180 | | -8h+6=-5h | | 9(10x-9)= | | 2/7-2/8 | | 7=16+x | | 28x^6+14x^3+49x^7= | | 11x+16+5y+7=180 | | 3/4x-2/3x-4=1/6x-7 | | -4a-7=1 | | .75(x)-9=27 | | 10x+20=9x+15 | | (13+2x)(8+2x)=153 | | 7p-2+14p= | | 3/8t-3/4=1/2t | | 102+6s+6s=s | | a/21=-10/7 | | 2(-1+7p)= | | -6x+2+20=-4x+10 | | V^1-V^0/t | | -4x-2(2x+10)=-16 | | 6(m-4)+3=33 | | 6(7t+1)-8=t-1(t+1) | | -9(9b-6)= | | 5(2y+5)+(-20y)= | | 2.8x+53.4=5.8-9.1x | | 5(m-4)+1=21 | | 3x-27y=30 | | 4n-10=3n+3 | | (4x-1)-(3x-4)= | | 1/5x-1/10x=7/2 | | 10(7+6r)= |